ANALISIS KEBIJAKAN PENDIDIKAN FULL DAY SCHOOL DALAM PEMBENTUKAN KARAKTER ANAK - Mustabsyirah, Mustabsyirah; Mardyawati, Mardyawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This article analyzes the Full Day School (FDS) policy in Indonesia, which is regulated by Permendikbud No. 23/2017, to evaluate its impact on character building in children. The purpose of this study is to identify the supporting and hindering factors in the implementation of FDS and to assess its effectiveness in holistic character development. The method used is a literature review (library research) by analyzing academic sources related to FDS policy, character education, and the Indonesian social context. The research findings reveal the positive impact of FDS in building discipline, responsibility, independence, cooperation, and tolerance through structured activities, collaborative projects, and extracurricular activities. The intensive school environment also minimizes exposure to negative external influences and strengthens the internalization of character values through the integration of religious education, local culture, and literacy. However, significant negative impacts were also identified: the risk of academic burnout due to excessive study time, which reduces children's motivation and creativity; reduced family involvement in instilling moral values; and inadequate infrastructure (insufficient facilities) and teacher competence (lack of training in character education methods). Although FDS has the potential to shape children's character, its success depends on strategic interventions: (1) context-based implementation reform (differentiated policies for urban/rural areas); (2) strengthening teacher capacity and integrated curriculum; (3) tripartite synergy between schools, families, and communities; and (4) ensuring children's psychological well-being. Without this multidimensional approach, FDS risks failing educational disparities and failing to achieve the goal of holistic character development. ABSTRAKKebijakan Full Day School (FDS) di Indonesia yang diatur melalui Permendikbud No. 23/2017 dianalisis dalam artikel ini untuk mengevaluasi dampaknya terhadap pembentukan karakter anak. Tujuan penelitian ini adalah mengidentifikasi faktor pendukung dan penghambat implementasi FDS serta mengkaji efektivitasnya dalam pengembangan karakter holistik. Metode yang digunakan adalah studi literatur (library research) dengan menganalisis sumber-sumber akademis terkait kebijakan FDS, pendidikan karakter, dan konteks sosial Indonesia. Hasil penelitian mengungkap dampak positif FDS dalam membangun disiplin, tanggung jawab, kemandirian, kerja sama, dan toleransi melalui kegiatan terstruktur, proyek kolaboratif, dan ekstrakurikuler. Lingkungan sekolah yang intensif juga meminimalkan paparan pengaruh negatif eksternal serta memperkuat internalisasi nilai-nilai karakter melalui integrasi pendidikan agama, budaya lokal, dan literasi. Namun, ditemukan pula dampak negatif signifikan, yaitu risiko burnout akademik akibat beban waktu belajar berlebihan yang menurunkan motivasi dan kreativitas anak, pengurangan peran keluarga dalam penanaman nilai moral, hingga ketidaksiapan infrastruktur dan fasilitas yang tidak memadai, dan kurangnya kompetensi guru dalam pendidikan karakter. Meskipun FDS berpotensi membentuk karakter anak, keberhasilannya bergantung pada: (1) reformasi implementasi berbasis konteks (diferensiasi kebijakan untuk daerah perkotaan/pedesaan); (2) penguatan kapasitas guru dan kurikulum terintegrasi; (3) sinergi tripartit sekolah-keluarga-komunitas; dan (4) penjaminan kesejahteraan psikologis anak. Tanpa penanganan multidimensi ini, FDS berisiko memperdalam ketimpangan pendidikan dan gagal mencapai tujuan pembentukan karakter utuh.